A method for mining over-limit patterns of low voltage in users based on hierarchical affinity propagation clustering - SHEN Shuhao; ZHONG Qing; XU Zhong; WANG Gang; LI Haifeng; WANG Longjun (电力工程技术)
Mining different over-limit patterns of the low voltage is very important to guide the management of low voltage issues in users. Due to the complexity and the ever-changing nature of voltage, the over-limit patterns of low voltage are always inherently unknown in users. A pattern mining method for low voltage in users based on hierarchical affinity propagation clustering (HAP) is proposed in this paper. Firstly, large-scale voltage data is clustered into several clusters using the HAP clustering algorithm, and these clusters are regarded as the different over-limit patterns of low voltage. Then, four indices are defined from two aspects of the duration and amplitude to characterize the features of the clusters. The features of the over-limit patterns are then drived by calculating the indices for each cluster. Finally, the proposed method is applied to a real dataset, effectively mining four over-limit patterns of low voltage. The characteristics of different patterns provide the important information for the supervision and analysis of low voltage issues in users, and the priorities of low voltage problems management in users can be well leveled.